Quantitave assessment of income distribution and poverty in the East Coast Region, Malaysia - Asfari, Noor Azian (2012)
This study investigated the implications of development on income distribution and poverty in the East Coast region of Malaysia. By using the data from the Household Income Survey (HIS) in 1999 and 2004, income distribution in the states of Kelantan, Terengganu and Pahang was analysed to show the extent of income inequality in the region which have the lowest percapita GOP in Malaysia. Income inequality was measured using the most popular measures namely; Lorenz curve, Gini coefficient and Atkinson's indices. Within the 5-year span, it is found that the development programs implemented by the government has successfully increased monthly income of the population and reduced income inequality in Kelantan and Terengganu. The incidence of poverty has also been reduced significantly in all states, with Kelantan showing the most improved level of poverty within those 5 years. It was also found that an increase in the age of the head of household and a female head of household negatively affect the take-home income, making them as the most crucial groups that requires government attention in the future SOCIO economic development programs to ensure that income inequality and poverty could be further reduced in the future.